2004
DOI: 10.1212/wnl.62.11.2010
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Parkinson disease in women

Abstract: An association between factors reducing estrogen stimulation during life and PD was found. These results support the hypothesis that endogenous estrogens play a role in the development of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
126
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(147 citation statements)
references
References 47 publications
14
126
3
3
Order By: Relevance
“…Increased PD risk was also reported in another study in relation to duration of reproductive life (age at menopause minus age at menarche) less than 36 years (OR 2.07, 95% CI 1.00-4.30) and total pregnancy time more than 30 months (OR 2.19, 95% CI 1.22-3.91) [648]. Similar to the first indicated study [647], no associations were observed for age at menopause, postmenopausal estrogen use, and age at menarche [648]. In contrast, however, this study reported lower PD risk associated with surgical menopause (OR 0.30, 95% CI 0.13-0.77) [648].…”
Section: Estrogensupporting
confidence: 71%
See 2 more Smart Citations
“…Increased PD risk was also reported in another study in relation to duration of reproductive life (age at menopause minus age at menarche) less than 36 years (OR 2.07, 95% CI 1.00-4.30) and total pregnancy time more than 30 months (OR 2.19, 95% CI 1.22-3.91) [648]. Similar to the first indicated study [647], no associations were observed for age at menopause, postmenopausal estrogen use, and age at menarche [648]. In contrast, however, this study reported lower PD risk associated with surgical menopause (OR 0.30, 95% CI 0.13-0.77) [648].…”
Section: Estrogensupporting
confidence: 71%
“…Similar to the first indicated study [647], no associations were observed for age at menopause, postmenopausal estrogen use, and age at menarche [648]. In contrast, however, this study reported lower PD risk associated with surgical menopause (OR 0.30, 95% CI 0.13-0.77) [648]. A hospital-based study using spouses of male PD cases or friends of cases as controls also observed no association between postmenopausal estrogen use and PD [649].…”
Section: Estrogensupporting
confidence: 53%
See 1 more Smart Citation
“…Women with Parkinson's disease tend to have an earlier menopause, are more likely to have undergone hysterectomy, and used estrogen therapy less frequently than control subjects (Benedetti et al, 2001). Ragonese et al (2004) suggested that factors reducing estrogen contribute to the development of Parkinson's disease (Ragonese et al, 2004). This was recently supported by the Observational Study of the Women's Health Initiative (WHI-OS) that employed 83,482 women.…”
Section: Estrogen and Parkinson's Disease 41 Introductionmentioning
confidence: 99%
“…There is much evidence for the relationship between an increase in overall morbidity and mortality and early or late ages of onset of the menopausal transition, e.g. an association of premature menopause (due to the subsequent oestrogen deficiency) with the increased risk of cardiovascular [11][12][13][14] and autoimmune diseases [14,15], osteoporosis [16,17], neurological diseases and psychiatric diseases [18,19] has been confirmed [11,14,15,[20][21][22][23], while women experiencing menopause at a late age are at a higher risk of breast cancer [24,25] and abdominal obesity [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%